Community memory projects and web 2.0 content-oriented libraries - Saorín, Tomás (Anuario ThinkEPI, 2011)
Reflection on the role of public libraries in the digital information environment. The appropriate digital content niche that concerns libraries working in a collaborative approach with other cultural and local institutions is defined. The need for community-oriented content and crowdsourcing is described. Libraries could act as mediators between local cultural agents to support information quality and licensing in social web sites.